Multi-species meta-analysis identifies transcriptional signatures associated with cardiac endothelial responses in the ischaemic heart - Li, Ziwen; Solomonidis, Emmanouil G; Berkeley, Bronwyn; Tang, Michelle Nga Huen; Stewart, Katherine Ross; Perez-Vicencio, Daniel; McCracken, Ian R; Spiroski, Ana-Mishel; Gray, Gillian A; Barton, Anna K; Sellers, Stephanie L; Riley, Paul R; et al. (Cardiovascular research, 2023)
Abstract Aim Myocardial infarction remains the leading cause of heart failure. The adult human heart lacks the capacity to undergo endogenous regeneration. New blood vessel growth is integral to regenerative medicine necessitating a comprehensive understanding of the pathways that regulate vascular regeneration. We sought to define the transcriptomic dynamics of coronary endothelial cells following ischaemic injuries in the developing and adult mouse and human heart and to identify new mechanistic insights and targets for cardiovascular regeneration. Methods and results We carried out a comprehensive meta-analysis of integrated single-cell RNA-sequencing data of coronary vascular endothelial cells from the developing and adult mouse and human heart spanning healthy and acute and chronic ischaemic cardiac disease. We identified species-conserved gene regulatory pathways aligned to endogenous neovascularization. We annotated injury-associated temporal shifts of the endothelial transcriptome and validated four genes: VEGF-C, KLF4, EGR1, and ZFP36. Moreover, we showed that ZFP36 regulates human coronary endothelial cell proliferation and defined that VEGF-C administration in vivo enhances clonal expansion of the cardiac vasculature post-myocardial infarction. Finally, we constructed a coronary endothelial cell meta-atlas, CrescENDO, to empower future in-depth research to target pathways associated with coronary neovascularization. Conclusion We present a high-resolution single-cell meta-atlas of healthy and injured coronary endothelial cells in the mouse and human heart, revealing a suite of novel targets with great potential to promote vascular regeneration, and providing a rich resource for therapeutic development. Graphical Abstract Graphical Abstract Graphical Abstract outlining the strategy for meta-analysis of integrated single cell and single nucleus RNA-sequencing studies of coronary endothelial cells in mice and humans during developmental and adult stages and in healthy and diseased states. This produced a vast resource of targets with a potential role in coronary vascular regeneration, which can be accessed through the CrescENDO meta-atlas. Specifically, we highlight species-conserved pathways, mapped temporal changes in endothelial cell gene expression in early and late disease stages, and also highlight developmental genes that are reactivated in the injured adult heart. We envisage that this will support future therapeutic strategies to promote coronary neovascularisation following myocardial infarction.